Formação de professores numa perspectiva ausubeliana e da Sequência Fedathi: contribuições da disciplina de estágio para a prática de alunos do curso de pedagogia - Rocha, Mirley Nádila Pimentel (2014)
The Brazil faces several education-related problems, according to the Programme for International Student Assessment (PISA), our country has a deficit in the areas of Reading, Mathematics and Science. PISA is an international initiative that evaluates the students in the range of 15 years, which is equivalent to the approximate period in which students completing primary education in most countries. In 2009, Brazil won the position of 57 (fifty-seventh) place in 65 (sixty-five) evaluated nations. We know that many economic, social and cultural factors influence school failure observed in the PISA assessment, thereby realize the importance in conducting surveys, most directly in the education sector, with respect to training and teaching activities in support of student learning, search an understanding of the educational process, which is a disadvantage in regard to learning. Therefore, we made a qualitative research, descriptive, exploratory, with field research characteristics (GIL, 2008) in the course of night pedagogy, the Faculty of Education (FACED), the Federal University of Ceará (UFC), seeking to check teacher training that takes place in the stage of discipline in Secondary School, in respect of the theoretical foundation with practice in the classroom, in order to investigate the contributions of Fedathi sequence, in teaching activities in curricular training, the course student pedagogy, after attend Internship discipline in Secondary School. For reasons of the goals of this research, we deem necessary a theoretical contribution aimed at training and teaching practice, analyzing the contributions of Tardif (2002) and Perrenoud (2002), and the integration of digital technologies in the educational process, with a focus on pedagogical mediation to use them in the perspective of Valente and Bustamante (2009), in order to promote the teaching-learning methodology, articulating the Sequence Fedathi, Borges Neto (2013), and meaningful learning, adopting a constructivist perspective Ausubel et al. (1980) articulated the use of concept maps Novak (2010), The survey data indicated as phase ownership results Position making and proof of Fedathi sequence, with a deficit in the development of hypotheses for the stages of maturation and solution, we highlight the need for further studies through conceptual maps, incorporating the assumptions of Meaningful Learning, for allocation of this methodology.